Obesity paradox in individuals with type 1 diabetes - Hamasaki, Hidetaka (Frontiers in Clinical Diabetes and Healthcare, 2025)
The obesity paradox describes a counterintuitive phenomenon where overweight or mildly obese individuals with chronic diseases show better survival compared to those with normal weight. While this paradox has been reported in conditions such as heart failure and type 2 diabetes, its presence in type 1 diabetes (T1D) remains uncertain. This mini review summarizes current evidence from large cohort studies and a meta-analysis examining the association between body mass index (BMI) and clinical outcomes in individuals with T1D. Most findings do not support a protective effect of higher BMI; instead, both underweight and obesity are associated with increased risks of cardiovascular events and all-cause mortality. Notably, some evidence suggests that individuals with advanced diabetic nephropathy or chronic kidney disease (CKD) may show the lowest mortality at mildly elevated BMI levels. However, these observations may reflect the limitations of using BMI alone to evaluate obesity. Given that individuals with T1D often have reduced skeletal muscle mass, and that those with advanced diabetic complications or comorbidities such as CKD or cancer may develop cachexia, body composition analysis is essential. Accurate assessment of fat mass, muscle mass, bone mass, and water content is critical for understanding obesity-related risks. Future research should integrate body composition metrics to improve risk stratification in T1D.